IMPLEMENTASI PROGRAM TAHFIDZ AL-QUR’AN DALAM MEMBENTUK KARAKTER SANTRI DI PONDOK PESANTREN TAHFIDZ AN-NAWAWI NGLABAN JOMBANG - Abror, Amirul; Syamsuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research seeks to analyze the execution of the Qur'an memorization initiative in developing students' character at Pondok Pesantren Tahfidz An-Nawawi Nglaban Jombang. This invesgation utilized a qualitative method based on a case study design. Information was gathered via monitoring, discussions, and records concerning the boarding education institution administrator, tahfidz educators, and learners. The findings suggest that character development is executed through talaqqi, takrir, muraja'ah, sima'an, memorization deposit activities, and disciplinary habituation. The characters developed include discipline, responsibility, patience, istiqamah, independence, and noble morals. Supporting factors include a conducive Islamic environment, teacher guidance, student motivation, and structured coaching programs. Meanwhile, inhibiting factors include laziness, boredom, lack of motivation, and outside environmental factors. The research concludes that the tahfidz program effectively contributes to character building and serves as an example of Islamic character learning based on Qur'anic values.